IMPLEMENTATION OF INTEGRATED STUNTING REDUCTION ACCELERATED POLICY IN WARU JAYA VILLAGE, BOGOR DISTRICT - Widiastuti, Nany; Tuti, Retnowati WD.; Samudra, Azhari Aziz; Satispi, Evi; Andiani, Devia (DIA: Jurnal Administrasi Publik, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life. According to the results of the Indonesian Toddler Nutrition Status Survey, the stunting rate in 2021 has again decreased to 24.4%, which is higher than the WHO standard of 20%. The prevalence of stunting in Waru Jaya Village in 2019 was 30.5%. The purpose of this research was to analyze the implementation of policies to accelerate the reduction of stunting in Waru Jaya Village, Bogor Regency, West Java. The research method used is descriptive qualitative method. Data was obtained through interviews with related parties and also from several official government websites. The data were analyzed using the policy implementation theory of Merilee S. Grindle. The results show that there is a Regional Government policy in the form of a Regent's Instruction related to accelerating the reduction of integrated stunting in Waru Jaya Village and it has been implemented properly as evidenced by a reduction in the stunting rate to 2.9% in 2021. The Regent's Instruction should be updated so that it is in line with Presidential Regulations. The implementation of the policy to accelerate the reduction of integrated stunting in Waru Jaya Village is going well because it is based on an integrated prevention and treatment policy even though there are a number of things that need to be improved.